2020
DOI: 10.21203/rs.3.rs-66218/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technology-based Health Solutions for Cancer Caregivers to Better Shoulder the Impact of COVID-19: A Systematic Review Protocol

Abstract: Background Cancer patients are particularly vulnerable to COVID-19, partially owing to their compromised immune systems and curbed or cut cancer healthcare services caused by the pandemic. As a result, cancer caregivers may have to shoulder triple crises: the COVID-19 pandemic, pronounced healthcare needs from the patient, and elevated need for care from within. While technology-based health interventions have the potential to address unique challenges cancer caregivers face amid COVID-19, limited insights are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…One area that has not been explored within the carer resilience literature, and yet has the potential to increase resilience in the context of social distancing, shielding and face-to-face support service closures, is technology-based support ( Newman et al, 2019 ). Research has revealed that telehealth services during COVID-19, such as medical video conferencing and psychoeducation, were associated with improved resilience and wellbeing in both patients and carers alike ( McGee et al, 2020 ; Su et al, 2020 ). One key mechanism through which technology-based services promote such positive outcomes is peer support.…”
Section: Introductionmentioning
confidence: 99%
“…One area that has not been explored within the carer resilience literature, and yet has the potential to increase resilience in the context of social distancing, shielding and face-to-face support service closures, is technology-based support ( Newman et al, 2019 ). Research has revealed that telehealth services during COVID-19, such as medical video conferencing and psychoeducation, were associated with improved resilience and wellbeing in both patients and carers alike ( McGee et al, 2020 ; Su et al, 2020 ). One key mechanism through which technology-based services promote such positive outcomes is peer support.…”
Section: Introductionmentioning
confidence: 99%
“…14 Family caregivers have also encountered numerous stressors during this pandemic; for example, they must shoulder substantial demands for care from family members with cancer and cope with these patients' psychological and physical care needs. 15 In a systematic review of 21 149 family caregivers of patients with cancer, the prevalence rates of anxiety and depression were 46.55% and 42.30%, respectively. 16 Researchers discovered that coronavirus safety procedures (eg, self-isolation, lockdowns, and social distancing) can put additional strain on family caregivers of patients with cancer.…”
mentioning
confidence: 99%
“…Furthermore, evidence has revealed that healthcare systems do not provide adequate digital healthcare services to meet their complicated health needs 14 . Family caregivers have also encountered numerous stressors during this pandemic; for example, they must shoulder substantial demands for care from family members with cancer and cope with these patients' psychological and physical care needs 15 . In a systematic review of 21 149 family caregivers of patients with cancer, the prevalence rates of anxiety and depression were 46.55% and 42.30%, respectively 16 .…”
mentioning
confidence: 99%
See 2 more Smart Citations